Global Policy Frameworks And Their Implications For Metrics - Wollenberg, Eva Karoline (2018)
The presentation Global Policy Frameworks And Their Implications For Metrics is by Lini Wollenberg, flagship leader of CCAFS Low Emissions Development. Presented at the WBCSD Climate Smart Agriculture workshop at the University of Vermont, Burlington, VT on 28 March 2018.